Antioxidant-mediated defense response of Carica papaya L. var. eksotika against a compatible Erwinia mallotivora strain BT-MARDI - Supian, Suhaina (2015)
Papaya dieback disease, caused by the bacterium Erwinia mallotivora, is the most devastating papaya disease in Malaysia. Most papaya cultivars in Malaysia are susceptible to this disease which suggests that the molecular basis of the interaction between these cultivars and the pathogen is based on a compatible interaction, leading to disease development. However, in certain pathosystems, such interaction could also develop moderate defense response mediated by antioxidant system. Hence, it was hypothesized that early defense response in compatible interaction of papaya and E. mallotivora is mediated by antioxidant system. Therefore, this study was aimed to determine the expression of antioxidant-related genes and proteins and activity of antioxidantrelated enzymes in the early response of Eksotika papaya to E. mallotivora infection. In addition, this study also optimized the inoculation procedures for artificial infection of Eksotika papaya with this pathogen. Two important parameters in the artificial infection of E. mallotivora, inoculum concentration and leaf position, affected significantly the disease development in papaya. The probability of the infection depends on the number of bacteria inoculated where greater number of bacteria is required to defeat host defenses as well as the position of leaf where lower or older leaf is less metabolically active thus, lead to higher susceptibility to this infection. Therefore, for efficient artificial infection of papaya with this pathogen, the use of second leaf from the top and inoculum concentration of 107 CFU/inoculation site was recommended. Using these optimized parameters, the inoculation of papaya with this pathogen was carried out and the inoculated leaf samples were collected at 0, 2, 4, 8, 12 and 24 h of post-infection (hpi). Following the bacterial challenge, through semi-quantitative reverse-transcription-PCR (RT-PCR) method, the expression of two selected antioxidant marker genes [superoxide dismutase (SOD) and peroxidase] was analyzed. SOD gene was found to be transiently up-regulated at 2 hpi whereas, peroxidase gene was up-regulated throughout the experimental period. Through enzyme assays, enzymatic activity of SOD and peroxidase also showed a significant progressive increase occurred after 8 hpi (pvalue< 0.05). These observations were further confirmed through protein profiling of the infected leaf proteome at 4 and 8 hpi using two dimensionalpolyacrylamide gel electrophoresis (2D-PAGE) and mass spectrometry analysis where a significant up-regulation of SOD protein at 4 hpi was observed (p-value<0.10). Overall, the findings in this study proved that antioxidant system is involved in early defense response of papaya to E. mallotivora infection which may suggest that this defense pathway is also activated in this compatible interaction. This study provides new insights into molecular mechanisms underlying this interaction.